2015
DOI: 10.4269/ajtmh.14-0547
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Among Urogenital, Intestinal, Skin, and Oral Infections in Pregnant and Lactating Panamanian Ngäbe Women: A Neglected Public Health Challenge

Abstract: Abstract. Interrelationships among bacteria, protozoa, helminths, and ectoparasites were explored in a cross-sectional survey of 213 pregnant and 99 lactating indigenous women. Prevalences in pregnancy and lactation, respectively, were: vaginitis (89.2%; 46.8%), vaginal trichomoniasis (75.3%; 91.1%), bacterial vaginosis (BV; 60.6%; 63.3%), hookworm (56.6%; 47.8%), asymptomatic bacteriuria/urinary tract infection (AB/UTI; 56.2%; 36.2%), cervicitis (33.3%; 6.3%), vaginal yeast (24.9%; 11.4%), Ascaris (32.5%; 17.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 64 publications
1
29
0
2
Order By: Relevance
“…Based on government statistics, 6.7% of institutional deliveries are low birthweight infants at the country level (33), whereas low birthweight rates are as high as 14% in the Ngäbe population (34). We have previously reported that pregnant women in our study had a high prevalence (>50%) of several vaginal and intestinal infections as well as oral, skin and urinary tract infections (35). Despite distribution of iron and micronutrient supplements by the Ministry of Health, >40% of these women had deficiencies of vitamins A, D and B 12 , and CRP was elevated in 16.4% of these women (32).…”
Section: Study Populationmentioning
confidence: 55%
See 2 more Smart Citations
“…Based on government statistics, 6.7% of institutional deliveries are low birthweight infants at the country level (33), whereas low birthweight rates are as high as 14% in the Ngäbe population (34). We have previously reported that pregnant women in our study had a high prevalence (>50%) of several vaginal and intestinal infections as well as oral, skin and urinary tract infections (35). Despite distribution of iron and micronutrient supplements by the Ministry of Health, >40% of these women had deficiencies of vitamins A, D and B 12 , and CRP was elevated in 16.4% of these women (32).…”
Section: Study Populationmentioning
confidence: 55%
“…Women were considered for the study if consulting for normal pregnancy follow up, and they did not present with signs of distress. The presence of HIV and gestational diabetes had been ruled-out by the Ministry of Health (35).…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work in an indigenous population living in conditions of extreme poverty in Panama revealed not only a range of bacterial, fungal, protozoan, helminth, and ectoparasite infections among pregnant and lactating women but also synergistic and antagonistic interactions among the various pathogens [42]. Furthermore, informal conversations with physicians highlighted the challenge they faced in relying on CRP as a marker of inflammation under these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, in humans, there is little evidence that pregnancy alters transmission risks for helminths,4,22 though a few results are suggestive of this possibility 23. Despite this, helminths and pregnancy might have synergistic effects on other health outcomes.…”
Section: Intersections Between Pregnancy and Helminth Infectionmentioning
confidence: 99%